Unlearning, wondering, listening routes for thinking about a dissenting art education (Palíndromo, 2023)
The present article presents the paths of the author in the construction of dissident pedagogical proposals, involving articulations between the artistic practice and the pedagogical practice in the Visual Arts Licentiate. In order to provide the students with these experiences, classes were designed in which theory and practice were not dissociated, but constantly nourished each other; fragmentations such as Art and Life, Education and Art, acting and thinking, were all put in parentheses. The provocation to think about art and dissident art education always came from daily concerns, which soon found in the methodologies used by the artists another issue-problem to be thought about. In these paths, with the unlearning from the artists' work and their practice, it was possible to understand that one path was certain: to deconstruct knowledge, to ask more than to answer, to learn to listen to what the dissident artistic practices are clamoring for and, only from this other way of unlearning without absolute and true answers, it becomes possible to reconstruct knowledge.
Keywords: Dissident art education; Art practice and teaching practice; Pedagogical practice; Bachelor of Visual Arts